Effects of mesoporous silica particle loading on the properties of PDMS-based mixed matrix membrane - Tomoya Yoshihara; Keishi Suga; Hikaru Namigata; Kanako Watanabe; Tom A.J. Welling; Kumiko Hayashi; Lester C. Geonzon; Koichi Mayumi; Daisuke Nagao (Chemical Engineering Journal Advances, 2025)
Mixed matrix membranes (MMMs), which combine the advantages of filler particles and polymer, are promising materials for gas separation. Polydimethylsiloxane (PDMS) has been widely studied as a matrix polymer for MMMs, because of its flexibility and unique gas permeation properties, such as CO2/N2 selectivity. As for the other component, mesoporous particulate materials have attracted attention as the fillers that enhance gas permeation. However, the effects of mesoporous particles loading in PDMS membranes have not been studied sufficiently so far. In this study, the gas permeability and CO2 selectivity of the PDMS incorporating mesoporous silica particles (PDMS/MPs) were evaluated. Self-standing membranes (PDMS or PDMS/MPs) were fabricated, wherein the ordered mesopore structures were maintained in the membranes. The mechanical properties were improved by loading MPs. PDMS/MPs membranes attained enhanced CO2 permeability of 3650 Barrer, corresponding to a permeance of 8.0 GPU, while mostly maintaining selectivity: CO2/N2 = 10.2, CO2/H2 = 4.6. Our investigations highlight the advantages of mesoporous silica particles, which can enhance the mechanical property and gas permeability of MMMs.